IMPLEMENTASI PENGENDALIAN KUALITAS MENGGUNAKAN PENDEKATAN SEVEN TOOLS PADA CV. PAKIS KARUNIA DI GRESIK - Selvi Wijaya; Fitri Novika Widjaja; Antonius Budhiman Setyawan (CALYPTRA, 2018)
The step of production process at CV. Pakis Karunia in Gresik, based on the type and amount of disability during the paper bag production process the company has experienced losses from the amount of production per month. Therefore, this study can be used to know implementation of quality control using seven tools. Analysis of quality control using seven tools such as check sheet, histograms, pareto diagrams, cause-effect diagrams, and control diagrams. The tools will be implemented into the CV. Pakis Karunia in Gresik. The results of histogram showing proportion defect in many variants. Fromcause-effect diagram the analysis, it can be seen the factors that cause defects in products derived from materials, machinery, human, work methods and environment, so that company can take corrective action to overcome it. From the analysis of the map control indicates that production is outside of the limits of control.